2011
DOI: 10.1161/circulationaha.110.011973
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation of Left Heart Valve Bioprostheses According to Age at Implantation

Abstract: Background-Evidence supporting the use of bioprostheses for heart valve replacement in young adults is accumulating.However, reoperation data, which may help guide clinical decision making in young patients, remains poorly defined in the literature. Methods and Results-We examined the need for reoperation in 3975 patients who underwent first-time bioprosthetic aortic valve replacement (AVR) (nϭ3152) or mitral valve replacement (MVR) (nϭ823). There were 895 patients below the age of 60 years at bioprosthesis im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 24 publications
2
40
0
5
Order By: Relevance
“…In terms of recommendations for the use of bioprosthetic valves, these excellent outcomes appear to support their use in patients at least from the age of 60 years, notably younger than the cutoff of 65 years retained in the international guidelines [24,25]. Indeed, even if patients younger than 60 years have a higher risk of reoperation, we think that the associated low mortality risk of the procedure versus the increased risk of hemorrhage secondary to anticoagulation can make the option to use the bioprosthetic valve an acceptable one for this population [26][27][28].…”
Section: Expected Valve Durability (Svd Reoperation Due To Svd)mentioning
confidence: 86%
“…In terms of recommendations for the use of bioprosthetic valves, these excellent outcomes appear to support their use in patients at least from the age of 60 years, notably younger than the cutoff of 65 years retained in the international guidelines [24,25]. Indeed, even if patients younger than 60 years have a higher risk of reoperation, we think that the associated low mortality risk of the procedure versus the increased risk of hemorrhage secondary to anticoagulation can make the option to use the bioprosthetic valve an acceptable one for this population [26][27][28].…”
Section: Expected Valve Durability (Svd Reoperation Due To Svd)mentioning
confidence: 86%
“…The existing studies consistently demonstrated a higher rate of freedom from reoperation in aortic positions: Chan et al [9] reported a 15-year freedom from reoperation of 78% following AVR and of 62% following MVR in patients >60 years of age, while the freedom from reoperation at 10 years was 91 and 76%, respectively, for the AVR and MVR groups in the study of Poirier et al [18]. Indeed, it is recommended that bioprosthesis use is optimal in the age group of ≥60 years for AVR and >70 years for MVR.…”
Section: Discussionmentioning
confidence: 99%
“…The second-generation Carpentier-Edwards Perimount (CE-P) bovine pericardial bioprosthesis (Edwards Lifesciences, Irvine, CA, USA) has shown excellent safety and efficacy in long-term clinical follow-up investigations [1,2,3,4,7,8]. In addition, age has been reported as an influential factor for bioprosthesis durability, survival, and the risks that are associated with reoperation [1,3,9]. In China, mechanical prostheses are still predominant for cardiac valve replacements in clinical practice; in fact, the patients' age at the time of implantation is relatively younger than in industrialized societies [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This report demonstrates the real world of valve literature: Most bioprosthetic valve studies are single-center, nonrandomized trials with relatively short follow-up that are conducted in middle-aged and elderly patients. Studies that examine the impact of age on outcomes include very few patients <50 years of age [8][9][10] and tend to examine differences between age strata within an elderly population. Only a tiny fraction of the published experience includes patients <30 years of age.…”
Section: Article See P 51mentioning
confidence: 99%